PENGARUH COVID 19 TERHADAP KREDIT BERMASALAH DI INDONESIA (Studi Kasus pada Bank BUKU I di Indonesia) - Kisti Yunia Indasari; Bintoro, Nugroho Suryo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aim to examine the influence of COVID in the form of new COVID cases, cumulative COVID cases, and COVID deaths. As well as capital ratios in the form of Regulatory Capital Ratio (CAR), Tier 1 Capital Ratio, and Equity Ratio with bank performance level control variables in the form of ROA, LDR, and Bank size. Also macroeconomic controls in the form of GDP, BI Rate, and Unemployment on Bad Perfoming Loans. This study used quantitative data analysis techniques using Panel Data (REM) methods. This research concludes that even though there has been a decrease in the rate of new COVID cases, the ratio of bad loans has increased significantly. Banks with larger equity ratios were able to increase the non-perfoming loan ratio at BUKU I baks during COVID crisis.